2006
DOI: 10.1080/00343400600632739
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about geographical knowledge spillovers and regional growth?: A survey of the literature

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
180
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(195 citation statements)
references
References 59 publications
5
180
0
10
Order By: Relevance
“…Converse to knowledge spillover models, models of cumulative causation consider knowledge to be a private good that is utilised by a clearly confined group of users (Myrdal, 1957;Döring and Schnellenbach, 2006). However, as Döring and Schnellenbach (2006) argue, both the knowledge spillover and cumulative causation theses can be criticised to some extent for their lack of realism.…”
Section: Inter-organisational Network and Knowledge Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Converse to knowledge spillover models, models of cumulative causation consider knowledge to be a private good that is utilised by a clearly confined group of users (Myrdal, 1957;Döring and Schnellenbach, 2006). However, as Döring and Schnellenbach (2006) argue, both the knowledge spillover and cumulative causation theses can be criticised to some extent for their lack of realism.…”
Section: Inter-organisational Network and Knowledge Flowmentioning
confidence: 99%
“…Knowledge may have the potential to spill over from one organisation to another, but knowledge access or acquisition is dependent on cumulative processes whereby 'new' incoming knowledge is utilisable only when there is the necessary complementary knowledge already in place in the receiving organisation (Döring and Schnellenbach, 2006). This is considered to require the development of absorptive capacity, defined as the ability to recognise the value of new, external knowledge, assimilate it, and apply it to commercial ends, i.e.…”
Section: Knowledge Spilloversmentioning
confidence: 99%
“…There seems to be a widespread consensus that also spillovers constitute an important type of and specific channel for knowledge transfer and that these externalities have a positive impact on innovation and growth ( Tödtling et al 2006). The mobility of highly skilled personnel (or the transfer of human capital) represents another core mechanism for the spilling over of (embodied) knowledge ( Arrow 1959;Matusik and Hill 1998;Argote and Ingram 2000;Rosenkopf and Almeida 2003;Moen 2005;Döring and Schnellenbach 2006).…”
mentioning
confidence: 99%
“…patents. These studies often find larger ranges for the knowledge spillovers, which can be up to 300 km (Döring and Schnellenbach, 2006), although for OECD countries, Keller (2002) finds it is 1200 km for the half-life distance of R&D spending! The third approach is based on case study, but where the distance is found to depend on the nature of the activity being studied (Cumbers and Mackinnon, 2004).…”
Section: The 'Region' and Appropriate Spatial Scalementioning
confidence: 99%
“…It suggests that the appropriate spatial scale is an empirical matter, but even here there is no agreement. Döring and Schnellenbach (2006) survey the literature and find "a wide-spread consensus that spatially confined knowledge-spillovers are an important empirical phenomenon" (p. 383), but that the "majority of studies refuse to quantify the range at all" (p. 384). In fact, not only is there is little agreement on the distance over which they occur, but uncertainty over the nature of the externality itself (see Roberts and Setterfield, 2007).…”
Section: The 'Region' and Appropriate Spatial Scalementioning
confidence: 99%